2016
DOI: 10.1002/cre2.32
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of occlusal dysesthesia utilizing prefrontal hemodynamic activity with slight occlusal interference

Abstract: Clinical diagnosis of occlusal dysesthesia (OD), also referred to as phantom bite syndrome, is currently based on the absence of objective occlusal discrepancy despite the persistent complaint of uncomfortable bite sensation. We previously demonstrated that the subjective feeling of occlusal discomfort generated by artificial occlusal interference can be objectively evaluated using prefrontal hemodynamic activity in young healthy individuals. The aim of this study was to investigate whether dental patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…Znaleziono 43 artykuły, z których po ocenie tytułów i streszczeń wyodrębniono 4 oryginalne prace, spełniające ustalone kryteria włączenia. [6][7][8][9] Przeglądając piśmiennictwo wybranych artykułów zakwalifikowano jeszcze jedną pracę. 10…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Znaleziono 43 artykuły, z których po ocenie tytułów i streszczeń wyodrębniono 4 oryginalne prace, spełniające ustalone kryteria włączenia. [6][7][8][9] Przeglądając piśmiennictwo wybranych artykułów zakwalifikowano jeszcze jedną pracę. 10…”
Section: Resultsunclassified
“…A total of forty-three articles were found, of which, after evaluation of the titles and abstracts, four original works were selected, meeting the predetermined inclusion criteria. [6][7][8][9] While reviewing the reference literature of selected articles, one more work was qualified. 10…”
Section: Materiał I Metodymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on proposals by Melis and Zawawi [1], the study population included OD patients who persistently complained of uncomfortable bite sensation for at least 6 months in the absence of dental occlusal discrepancies, such as centric prematurity or nonworking interference, or when the complaints were disproportionate to those conditions [14]. Fifteen OD patients, 8 males and 7 females, with a mean age of 49.9 ± 16.1 years were investigated, and the results were compared to those obtained from 15 age-and gender-matched (Fisher's exact test and Z test) HC subjects (8 males, 7 females; age 39.3 ± 15.3 years).…”
Section: Participantsmentioning
confidence: 99%
“…For example, Su et al [13] reported a positive relationship between somatization subscale and bilateral superior medial prefrontal activities in patients with somatoform pain disorders. With regard to somatization in the oral region, Ono et al [14] recently examined prefrontal activity and tooth contact sensation in relation to tooth grinding, and they found that increased prefrontal hemodynamic responses may reflect top-down attention and/or self-regulation against uncomfortable somatosensory input induced in OD patients. In addition, Umezaki et al [15] reported that temporal hyperperfusion was improved along with alleviation of oral cenesthopathy in a clinical study.…”
Section: Introductionmentioning
confidence: 99%